2015
DOI: 10.3923/pjbs.2015.191.195
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Iron Deficiency Anaemia Among School Children in Kenitra, Northwest of Morocco

Abstract: Iron deficiency anaemia is an important health problem in Morocco. This study was conducted to estimate the prevalence of anaemia among school children in Kenitra. The sample represents school children of all educational levels and age ranged between 6-15 years. The level of hemoglobin, haematocrit, mean corpuscular volume, mean corpuscular hemoglobin and mean corpuscular hemoglobin concentration was measured in a group of 271 school children. The seric iron was assessed and anaemia was defined when hemoglobin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
6
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 18 publications
7
6
3
Order By: Relevance
“…The difference between sexes in hemoglobin concentration and the prevalence of anemia was also observed in previous studies [11,24,25]. However, some studies reported no significant difference in the mean hemoglobin concentration between boys and girls, and the reason for this could be the different sample sizes and subjects [26,27].…”
Section: Discussionsupporting
confidence: 72%
“…The difference between sexes in hemoglobin concentration and the prevalence of anemia was also observed in previous studies [11,24,25]. However, some studies reported no significant difference in the mean hemoglobin concentration between boys and girls, and the reason for this could be the different sample sizes and subjects [26,27].…”
Section: Discussionsupporting
confidence: 72%
“…However, age and gender differences as well as the other two STH intensities did not increase the risk of anaemia. In agreement with the present report, some studies in Ethiopia revealed consistent reports [ 8 , 43 ], but this goes not in line with findings from Kenya [ 34 ] and Morocco [ 33 ], in which they found that age and sex had association with anaemia.…”
Section: Main Textsupporting
confidence: 77%
“…The prevalence of anaemia was 15.4% in this study, which does not markedly differ from other studies carried out in northern Ethiopia (11%) [ 31 ], north-western Uganda 11.8% [ 32 ] and northwestern Morocco (16.2%) [ 33 ]. But it was lower than the reports from Shimbit, Ethiopia (25.8%) [ 6 ]; Jimma, Ethiopia (37.6%) [ 4 ]; Kenya (28.8%) [ 34 ]; Rwanda (30.9%) [ 35 ] and Upper Egypt (59.3%) [ 36 ].…”
Section: Main Textcontrasting
confidence: 72%
“…Anemia is most commonly seen in girls (81.48%) in our study due to menstrual problems. The overall proportion of anemia among the study population was found to be 25% and is similar to a study conducted by Achouri et al (2015) where the proportion of anemic children was 16.2% (Achouri et al, 2015).…”
Section: Discussionsupporting
confidence: 67%